Análise das práticas de governança da tecnologia da informação (TI) à luz dos modelos COBIT e BSC em empresa contratante de serviços de outsourcing - Targa, Magda Santos (Universidade do Vale do Rio do Sinos, 2009)
IT services have been more and more perceived as a competitive advantage instrument, and its influence should continue climbing up the charts. These and other factors lead the companies to review their IT management models. Lately, IT governance has turned into a subject of investigation interest and it has an outward approach, which is related to the business demands and consequent strategic alignment needs, and an internal approach, that refers to the IT organization and IT processes. The use of models can help this governance, because they lead to conformity, systemize e remove uncertainty. In this context, this dissertation assesses the IT governance practices, what involves organization and third-part human resources allocation in health business company, considering COBIT e BSC governance models.
Keywords: BSC; COBIT; modelo de governança; terceirização de TI; governança de TI; governance framework; outsourcing; IT governance; Ciências Sociais Aplicadas